Pemanfaatan JBclass untuk Meningkatkan Motivasi Belajar Geografis Siswa Selama Masa Pandemi Covid-19 di Resmi Bisma Paket C Kalimanah - Desi Wulandari; Sriyanto (UM Purwokerto Press, 2021)
Motivation to learn geography for class X Official Bisma Paket C Kalimanah students by utilizing JBClass during the COVID19 pandemic. This paper is a best practice that is carried out in the odd semester of the 2020/2021 school year. The target of this best practice is class X official Bisma Paket C Kalimanah students. The steps for solving problems in this best practice are the use of JBClass as online learning during the COVID-19 pandemic. The instruments of this best practice are the material features, assignments, evaluations and recap of the scores that are on the JBClass. The best practice results show that the use of JBClass in online learning during the COVID-19 pandemic can increase the motivation to learn Geogarafi for class X Official Bisma Paket C Kalimanah for the 2020/2021 school year. Increased motivation to learn geography can be seen from the increase in the average score of assignments and evaluations per class and the timeliness of the work in taking lessons with JBClass during the COVID-19 pandemic.